2016
DOI: 10.1590/s0102-865020160070000006
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity ultrasound therapy induces angiogenesis and persistent inflammation in the chronic phase of the healing process of third degree burn wounds experimentally induced in diabetic and non-diabetic rats

Abstract: PURPOSE:To evaluate the effects of low intensity ultrasound on the healing process of third degree burn wounds in experimentally induced diabetic Wistar rats. METHODS:One hundred rats were divided into: control group; non-diabetic treated group; diabetic control group; diabetic treated group. The therapy was performed with a 3MHz ultrasound application, pulsed emission at 100Hz frequency, modulated at 20% with a dosage of 0.5W/cm 2 during three minutes throughout 30 days. The surgical debridement of the wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…The proposed mechanism for its efficacy in chronic wounds include the ultrasound-generated mechanical energy stimulating signal transduction pathways involved in wound healing, that is, leukocyte adhesion, growth factor generation, fibroblast proliferation, and collagen production. [35][36][37][38][39] NLFU induces vibration and cavitation instigates acoustic streaming and generates micron-sized bubbles in the tissues and causes fluids to move along the boundaries of sound wave in the cell membranes, resulting in alteration of cellular function, enhanced protein synthesis, and also increased permeability of the cell membranes and vascular walls. 26,38 Increased macrophage responsiveness, increased fibrinolysis, and increased nitric oxide are other ultrasoundinduced cellular effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed mechanism for its efficacy in chronic wounds include the ultrasound-generated mechanical energy stimulating signal transduction pathways involved in wound healing, that is, leukocyte adhesion, growth factor generation, fibroblast proliferation, and collagen production. [35][36][37][38][39] NLFU induces vibration and cavitation instigates acoustic streaming and generates micron-sized bubbles in the tissues and causes fluids to move along the boundaries of sound wave in the cell membranes, resulting in alteration of cellular function, enhanced protein synthesis, and also increased permeability of the cell membranes and vascular walls. 26,38 Increased macrophage responsiveness, increased fibrinolysis, and increased nitric oxide are other ultrasoundinduced cellular effects.…”
Section: Discussionmentioning
confidence: 99%
“…26,38 Increased macrophage responsiveness, increased fibrinolysis, and increased nitric oxide are other ultrasoundinduced cellular effects. 38,39 Ultrasound energy is also postulated to cause reduction of edema, inhibition of bacterial colonization, reduction of bacterial bioburden, and preventing biofilm formation. 37 Another critical factor for tissue repair and regeneration in chronic wounds is neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Fantinati et al investigated chronic third-degree burn wounds and reported that low-intensity ultrasound could control the extent of tissue necrosis, enhance granulation tissue formation, as well as accelerate wound closure (via contraction). They suggested that ultrasound would have useful effects on the inflammatory and proliferative phases in burn treatment process; but could induce undesirable angiogenesis as well as inflammation in the remodeling phase [136].…”
Section: Antimicrobial Light and Ultrasound-based Wound Therapymentioning
confidence: 99%
“…In addition, intergroup analysis (ND and D groups) showed less bone loss in the D group treated with SRP+SDT compared to the ND group treated with SRP. This could be explained by the ability of ultrasound to promote angiogenesis and collagen synthesis in damaged areas [26,27]. Gu XQ et al found that low-intensity pulsed ultrasound could facilitate the calcium salt deposition as well as new bone maturation [28].…”
Section: Histological Analysismentioning
confidence: 99%